A polymer solid electrolyte coated modified silicon-based negative electrode material and solid-state battery

By using a polymer solid electrolyte layer to cover the surface of the silicon-based negative electrode material, the problem of volume expansion and powderization of the silicon-based material during the charging and discharging process is solved, the cycle stability and charging and discharging performance of the battery are improved, and the energy density and safety of the battery are significantly improved.

CN119764363APending Publication Date: 2025-04-04ZHONGKE RONNENG (YANCHENG) TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411688340.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The volume expansion and powderization problems of silicon-based negative electrode materials during charging and discharging lead to a degradation of battery circulation performance. The existing polymer solid electrolyte coating materials have problems such as poor conductivity and low lithium ion transmission efficiency.

Method used

The polymer solid electrolyte layer is made of polyethylene glycol, polyethylene oxide or its copolymer mixed with lithium salt, plasticizer and crosslinking agent. The lithium salt is bistrifluoromethanesulfonylimide lithium LiTFSI, the plasticizer is propylene carbonate or dimethyl carbonate, and the crosslinking agent is dimethyl sulfoxide or ethylene glycol dimethacrylate. It is coated on the surface of the silicon-based material by electrophoretic deposition method to form a polymer solid electrolyte coating layer of 5-50nm thick.

Benefits of technology

Effectively alleviate the volume expansion of silicon-based materials during lithium embedding, improve the cycle stability and charge and discharge performance of the battery, significantly improve the energy density of the battery, and enhance the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764363A_ABST
    Figure CN119764363A_ABST
Patent Text Reader

Abstract

The present invention discloses a silicon-based negative electrode material coated and modified by a polymer solid electrolyte, comprising a silicon-based material and a polymer solid electrolyte layer coated on the surface of the silicon-based material; the present invention relates to the technical field of new energy materials. The silicon-based negative electrode material and solid-state battery coated and modified by a polymer solid electrolyte can effectively alleviate the volume expansion of the silicon-based material during the lithium insertion process through the polymer solid electrolyte coating layer, maintain the integrity of the negative electrode structure, thereby improving the cycle stability of the battery, and the polymer solid electrolyte coating layer has excellent lithium ion conductivity, which can significantly reduce the transmission resistance of lithium ions between the negative electrode and the electrolyte, and improve the charge and discharge performance of the battery. By optimizing the combination of the negative electrode material and the solid electrolyte, and improving the cycle stability and charge and discharge performance of the battery, the energy density of the battery can be significantly improved, and the use of the solid electrolyte avoids the potential safety hazards caused by the liquid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a silicon-based negative electrode material coated with a polymer solid electrolyte and a solid-state battery. Background Art

[0002] With the rapid development of new energy industry, the demand for high-performance lithium-ion batteries is growing. Silicon-based negative electrode materials have become the ideal choice for the next generation of lithium-ion battery negative electrode materials due to their high theoretical specific capacity. However, the volume expansion and pulverization of silicon-based materials during the charging and discharging process lead to a significant decrease in the battery cycle performance. In order to improve the cycle stability of silicon-based negative electrodes and the energy density of batteries, researchers have tried a variety of methods, such as nano-sizing, composite, surface coating, etc. Among them, surface coating technology has attracted much attention because of its simplicity and significant effect.

[0003] Although traditional coating materials such as carbon and oxides can alleviate the volume expansion of silicon-based materials to a certain extent, they have problems such as poor conductivity and low lithium ion transmission efficiency. Polymer solid electrolytes, as a new type of coating material, have excellent lithium ion conductivity and mechanical strength, and can effectively protect silicon-based negative electrode materials. However, the polymer solid electrolyte coated modified silicon-based negative electrode materials on the market still have problems such as unstable performance and short cycle life, and further improvement is urgently needed. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a polymer solid electrolyte coated modified silicon-based negative electrode material and a solid-state battery, which solves the problems mentioned in the above background technology.

[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: a polymer solid electrolyte coated modified silicon-based negative electrode material, comprising a silicon-based material and a polymer solid electrolyte layer coated on the surface of the silicon-based material; the polymer solid electrolyte layer is a mixture of polyethylene glycol, polyethylene oxide or its copolymer with a lithium salt, a plasticizer and a cross-linking agent, the lithium salt is lithium bistrifluoromethanesulfonyl imide LiTFSI, the plasticizer is one of propylene carbonate and dimethyl carbonate, and the cross-linking agent is one of dimethyl sulfoxide and ethylene glycol dimethacrylate.

[0006] Preferably, the method further comprises an oxide coating layer, wherein the oxide coating layer is located between the silicon-based material and the polymer solid electrolyte layer, and the thickness of the polymer solid electrolyte layer is 5-50 nm.

[0007] A high-performance solid-state battery using the silicon-based negative electrode material described above also includes a positive electrode and a solid electrolyte; the positive electrode is selected from one of lithium metal, lithium cobalt oxide, and lithium nickel manganese cobalt oxide, and the solid electrolyte is selected from one of a sulfide solid electrolyte and an oxide solid electrolyte.

[0008] Preferably, the method for preparing the polymer solid electrolyte coated modified silicon-based negative electrode material specifically comprises the following steps:

[0009] S1. Pretreatment of silicon-based negative electrode materials: select silicon powder with a purity of not less than 99.9% as raw material, and use a high-energy ball mill for ball milling treatment, the ball milling speed is 200-500r / min, the ball milling time is 3-10 hours, so that the silicon powder particle size is evenly distributed between 50-200nm, the ball milled silicon powder is screened, and the screened silicon particles are placed in an oxygen atmosphere for heat treatment at a temperature of 500-700°C for 1-3 hours. During the heat treatment process, the oxygen flow rate is controlled at 10-50sccm to ensure the formation of a uniform and dense silicon dioxide film, forming a silicon dioxide film with a thickness of 1-5nm;

[0010] S2. Preparation of polymer solid electrolyte coating layer: Mix the polymer matrix material with lithium salt, add an appropriate amount of solvent and cross-linking agent, and form a uniform polymer electrolyte solution under stirring at a speed of 450-500rpm for 1-2 hours. Place the pretreated silicon particles in the polymer electrolyte solution, and uniformly disperse the silicon particles in the solution by mechanical stirring. The mixing and stirring temperature is 45-55°C for 1.5-2.5 hours. The polymer electrolyte solution is coated on the surface of the silicon particles by electrophoretic deposition to form a uniform polymer solid electrolyte coating layer. The coated silicon particles are dried to remove the solvent and uncured polymer, and then cured in an inert gas atmosphere at a temperature of 80-150°C for 1-6 hours to obtain a modified silicon-based negative electrode material.

[0011] S3. Assembly of solid-state batteries: Use modified silicon-based negative electrode materials as negative electrodes, in combination with suitable positive electrode materials and solid electrolytes. The positive electrode materials can be prepared into positive electrode sheets by coating, pressing or electrochemical deposition. Assemble the negative electrode, positive electrode and solid electrolyte into solid-state batteries in a predetermined order and structure, seal them by laser welding, and perform performance tests on the assembled solid-state batteries, including cycle stability tests, energy density tests and safety performance tests.

[0012] Preferably, in S1, a ball milling operation is performed to remove oversized or undersized particles to ensure the uniformity of the particle size of the silicon particles. The pretreatment operation is performed to improve the binding force and stability between the silicon particles and the polymer solid electrolyte. During the screening process, a vibrating screening machine is used for screening.

[0013] Preferably, in S2, the thickness of the coating layer can be controlled by adjusting the concentration of the polymer electrolyte solution, the coating time and the coating method, and is generally between 5-50 nm.

[0014] Preferably, in S3, the positive electrode material is one of lithium metal, lithium cobalt oxide, and lithium nickel manganese cobalt oxide, and the solid electrolyte is one of a sulfide solid electrolyte and an oxide solid electrolyte.

[0015] Preferably, the solid electrolyte can be prepared into an electrolyte membrane or electrolyte layer by hot pressing, cold pressing or solvent volatilization. During the preparation of the positive electrode material, a conductive agent and a binder can be added as needed to improve the conductivity and mechanical strength of the positive electrode sheet. During the preparation of the solid electrolyte, the ion conductivity and mechanical properties of the solid electrolyte can be optimized by adjusting parameters such as the raw material ratio, preparation process and heat treatment conditions.

[0016] Beneficial Effects

[0017] The invention provides a polymer solid electrolyte coated modified silicon-based negative electrode material and a solid-state battery. Compared with the prior art, the present invention has the following beneficial effects: the polymer solid electrolyte coated modified silicon-based negative electrode material and solid-state battery, the polymer solid electrolyte layer is a mixture of polyethylene glycol, polyethylene oxide or its copolymer and lithium salt, plasticizer and cross-linking agent, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide LiTFSI, the plasticizer is one of propylene carbonate and dimethyl carbonate, the cross-linking agent is one of dimethyl sulfoxide and ethylene glycol dimethacrylate, the polymer solid electrolyte coating layer can effectively alleviate the volume expansion of the silicon-based material during the lithium insertion process, maintain the integrity of the negative electrode structure, thereby improving the cycle stability of the battery, the polymer solid electrolyte coating layer has excellent lithium ion conductivity, can significantly reduce the transmission resistance of lithium ions between the negative electrode and the electrolyte, and improve the charge and discharge performance of the battery, by optimizing the combination of the negative electrode material and the solid electrolyte, and improving the cycle stability and charge and discharge performance of the battery, the energy density of the battery can be significantly improved, and the use of the solid electrolyte avoids the potential safety hazards of the liquid electrolyte, such as leakage, fire, etc., thereby improving the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a flow chart of the steps of the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] See also Figure 1 The present invention provides three technical solutions: a polymer solid electrolyte coated modified silicon-based negative electrode material, comprising a silicon-based material and a polymer solid electrolyte layer coated on the surface of the silicon-based material; the polymer solid electrolyte layer is a mixture of polyethylene glycol, polyethylene oxide or a copolymer thereof with a lithium salt, a plasticizer and a cross-linking agent, the lithium salt is lithium bistrifluoromethanesulfonyl imide LiTFSI, the plasticizer is one of propylene carbonate and dimethyl carbonate, and the cross-linking agent is one of dimethyl sulfoxide and ethylene glycol dimethacrylate.

[0021] The present invention further comprises an oxide coating layer, wherein the oxide coating layer is located between the silicon-based material and the polymer solid electrolyte layer, and the thickness of the polymer solid electrolyte layer is 5-50 nm.

[0022] A high-performance solid-state battery using the silicon-based negative electrode material described above also includes a positive electrode and a solid electrolyte; the positive electrode is selected from one of lithium metal, lithium cobalt oxide, and lithium nickel manganese cobalt oxide, and the solid electrolyte is selected from one of a sulfide solid electrolyte and an oxide solid electrolyte.

[0023] In the present invention, a method for preparing a polymer solid electrolyte coated modified silicon-based negative electrode material specifically includes the following embodiments:

[0024] Embodiment 1

[0025] S1. Pretreatment of silicon-based negative electrode materials: select silicon powder with a purity of not less than 99.9% as raw material, and use a high-energy ball mill for ball milling treatment. The ball milling speed is 350r / min, and the ball milling time is 7 hours, so that the silicon powder particle size is evenly distributed between 125nm, and the silicon powder after ball milling is screened. The screened silicon particles are placed in an oxygen atmosphere for heat treatment at a temperature of 600°C for 2 hours. During the heat treatment process, the oxygen flow rate is controlled at 30sccm to ensure the formation of a uniform and dense silicon dioxide film, forming a silicon dioxide film with a thickness of 3nm;

[0026] S2. Preparation of polymer solid electrolyte coating layer: Mix the polymer matrix material with lithium salt, add an appropriate amount of solvent and cross-linking agent, and form a uniform polymer electrolyte solution under stirring at a speed of 475 rpm for 1.5 hours. Place the pretreated silicon particles in the polymer electrolyte solution, and uniformly disperse the silicon particles in the solution by mechanical stirring. The mixing and stirring temperature is 47°C for 2 hours. The polymer electrolyte solution is coated on the surface of the silicon particles by electrophoretic deposition to form a uniform polymer solid electrolyte coating layer. The coated silicon particles are dried to remove the solvent and uncured polymer, and then cured in an inert gas atmosphere at a temperature of 105°C for 3 hours to obtain a modified silicon-based negative electrode material.

[0027] S3. Assembly of solid-state batteries: Use modified silicon-based negative electrode materials as negative electrodes, in combination with suitable positive electrode materials and solid electrolytes. The positive electrode materials can be prepared into positive electrode sheets by coating, pressing or electrochemical deposition. Assemble the negative electrode, positive electrode and solid electrolyte into solid-state batteries in a predetermined order and structure, seal them by laser welding, and perform performance tests on the assembled solid-state batteries, including cycle stability tests, energy density tests and safety performance tests.

[0028] Embodiment 2

[0029] S1. Pretreatment of silicon-based negative electrode materials: select silicon powder with a purity of not less than 99.9% as raw material, and use a high-energy ball mill for ball milling treatment. The ball milling speed is 200r / min, and the ball milling time is 3 hours, so that the silicon powder particle size is evenly distributed between 50nm, and the silicon powder after ball milling is screened. The screened silicon particles are placed in an oxygen atmosphere for heat treatment at a temperature of 500°C for 1 hour. During the heat treatment process, the oxygen flow rate is controlled at 10sccm to ensure the formation of a uniform and dense silicon dioxide film, forming a silicon dioxide film with a thickness of 1nm;

[0030] S2. Preparation of polymer solid electrolyte coating layer: Mix the polymer matrix material with lithium salt, add an appropriate amount of solvent and cross-linking agent, and form a uniform polymer electrolyte solution under stirring at a speed of 450 rpm for 1 hour. Place the pretreated silicon particles in the polymer electrolyte solution, and uniformly disperse the silicon particles in the solution by mechanical stirring. The mixing and stirring temperature is 45°C for 1.5 hours. The polymer electrolyte solution is coated on the surface of the silicon particles by electrophoretic deposition to form a uniform polymer solid electrolyte coating layer. The coated silicon particles are dried to remove the solvent and uncured polymer, and then cured in an inert gas atmosphere at a temperature of 80°C for 1 hour to obtain a modified silicon-based negative electrode material.

[0031] S3. Assembly of solid-state batteries: Use modified silicon-based negative electrode materials as negative electrodes, in combination with suitable positive electrode materials and solid electrolytes. The positive electrode materials can be prepared into positive electrode sheets by coating, pressing or electrochemical deposition. Assemble the negative electrode, positive electrode and solid electrolyte into solid-state batteries in a predetermined order and structure, seal them by laser welding, and perform performance tests on the assembled solid-state batteries, including cycle stability tests, energy density tests and safety performance tests.

[0032] Embodiment 3

[0033] S1. Pretreatment of silicon-based negative electrode materials: select silicon powder with a purity of not less than 99.9% as raw material, and use a high-energy ball mill for ball milling treatment. The ball milling speed is 500r / min and the ball milling time is 10 hours. Make the silicon powder particle size uniformly distributed between 200nm, screen the silicon powder after ball milling, and place the screened silicon particles in an oxygen atmosphere for heat treatment at a temperature of 700°C for 3 hours. During the heat treatment process, the oxygen flow rate is controlled at 50sccm to ensure the formation of a uniform and dense silicon dioxide film, forming a silicon dioxide film with a thickness of 5nm;

[0034] S2. Preparation of polymer solid electrolyte coating layer: Mix the polymer matrix material with lithium salt, add an appropriate amount of solvent and cross-linking agent, and form a uniform polymer electrolyte solution under stirring. The stirring speed is 500 rpm and the stirring time is 2 hours. The pretreated silicon particles are placed in the polymer electrolyte solution, and the silicon particles are uniformly dispersed in the solution by mechanical stirring. The mixing and stirring temperature is 55°C and the time is 2.5 hours. The polymer electrolyte solution is coated on the surface of the silicon particles by electrophoretic deposition to form a uniform polymer solid electrolyte coating layer. The coated silicon particles are dried to remove the solvent and uncured polymer, and then cured in an inert gas atmosphere at a temperature of 150°C for 6 hours to obtain a modified silicon-based negative electrode material;

[0035] S3. Assembly of solid-state batteries: Use modified silicon-based negative electrode materials as negative electrodes, in combination with suitable positive electrode materials and solid electrolytes. The positive electrode materials can be prepared into positive electrode sheets by coating, pressing or electrochemical deposition. Assemble the negative electrode, positive electrode and solid electrolyte into solid-state batteries in a predetermined order and structure, seal them by laser welding, and perform performance tests on the assembled solid-state batteries, including cycle stability tests, energy density tests and safety performance tests.

[0036] Effect Example

[0037] The solid-state batteries provided by Examples 1-3 and Comparative Example (conventional solid-state batteries on the market) were subjected to the following performance tests for capacity testing and cycle testing, and the test results are shown in the following table:

[0038]

[0039] It can be seen from the above table that the polymer solid electrolyte coating can effectively alleviate the volume expansion of silicon-based materials during the lithium insertion process, maintain the integrity of the negative electrode structure, and thus improve the cycle stability of the battery. The polymer solid electrolyte coating has excellent lithium ion conductivity, which can significantly reduce the transmission resistance of lithium ions between the negative electrode and the electrolyte, and improve the charge and discharge performance of the battery. By optimizing the combination of negative electrode materials and solid electrolytes, and improving the cycle stability and charge and discharge performance of the battery, the energy density of the battery can be significantly improved. The use of solid electrolytes avoids the potential safety hazards of liquid electrolytes, such as leakage, fire, etc., and improves the safety of the battery.

[0040] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0041] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0042] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A silicon-based negative electrode material coated with a polymer solid electrolyte, characterized in that: It includes a silicon-based material and a polymer solid electrolyte layer coated on the surface of the silicon-based material; the polymer solid electrolyte layer is a mixture of polyethylene glycol, polyethylene oxide or its copolymer with a lithium salt, a plasticizer and a cross-linking agent, the lithium salt is lithium bistrifluoromethanesulfonyl imide LiTFSI, the plasticizer is one of propylene carbonate and dimethyl carbonate, and the cross-linking agent is one of dimethyl sulfoxide and ethylene glycol dimethacrylate.

2. The polymer solid electrolyte coated modified silicon-based negative electrode material according to claim 1, characterized in that: It also includes an oxide coating layer, which is located between the silicon-based material and the polymer solid electrolyte layer. The thickness of the polymer solid electrolyte layer is 5-50 nm.

3. A high-performance solid-state battery using the silicon-based negative electrode material according to any one of claims 1 to 2, characterized in that: It also includes a positive electrode and a solid electrolyte; the positive electrode is selected from one of lithium metal, lithium cobalt oxide, and lithium nickel manganese cobalt oxide, and the solid electrolyte is selected from one of a sulfide solid electrolyte and an oxide solid electrolyte.

4. A polymer solid electrolyte coated modified silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method specifically comprises the following steps: S1. Pretreatment of silicon-based negative electrode materials: select silicon powder with a purity of not less than 99.9% as raw material, and use a high-energy ball mill for ball milling treatment. The ball milling speed is 200-500r / min, and the ball milling time is 3-10 hours, so that the silicon powder particle size is evenly distributed between 50-200nm, and the silicon powder after ball milling is screened. The screened silicon particles are placed in an oxygen atmosphere for heat treatment at a temperature of 500-700°C for 1-3 hours. During the heat treatment process, the oxygen flow rate is controlled at 10-50sccm to ensure the formation of a uniform and dense silicon dioxide film, forming a silicon dioxide film with a thickness of 1-5nm; S2. Preparation of polymer solid electrolyte coating layer: Mix the polymer matrix material with lithium salt, add an appropriate amount of solvent and cross-linking agent, and form a uniform polymer electrolyte solution under stirring at a speed of 450-500rpm for 1-2 hours. Place the pretreated silicon particles in the polymer electrolyte solution, and uniformly disperse the silicon particles in the solution by mechanical stirring. The mixing and stirring temperature is 45-55°C for 1.5-2.5 hours. The polymer electrolyte solution is coated on the surface of the silicon particles by electrophoretic deposition to form a uniform polymer solid electrolyte coating layer. The coated silicon particles are dried to remove the solvent and uncured polymer, and then cured in an inert gas atmosphere at a temperature of 80-150°C for 1-6 hours to obtain a modified silicon-based negative electrode material. S3. Assembly of solid-state batteries: Use modified silicon-based negative electrode materials as negative electrodes, in combination with suitable positive electrode materials and solid electrolytes. The positive electrode materials can be prepared into positive electrode sheets by coating, pressing or electrochemical deposition. Assemble the negative electrode, positive electrode and solid electrolyte into solid-state batteries in a predetermined order and structure, seal them by laser welding, and perform performance tests on the assembled solid-state batteries, including cycle stability tests, energy density tests and safety performance tests.

5. The method for preparing a polymer solid electrolyte coated modified silicon-based negative electrode material according to claim 4, characterized in that: In S1, a ball milling operation is performed to remove oversized or undersized particles to ensure the uniformity of the particle size of the silicon particles. The pretreatment operation is performed to improve the bonding force and stability between the silicon particles and the polymer solid electrolyte. During the screening process, a vibrating screening machine is used for screening.

6. The method for preparing a polymer solid electrolyte coated modified silicon-based negative electrode material according to claim 4, characterized in that: In S2, the thickness of the coating layer can be controlled by adjusting the concentration of the polymer electrolyte solution, the coating time and the coating method, and is generally between 5-50 nm.

7. The method for preparing a polymer solid electrolyte coated modified silicon-based negative electrode material according to claim 4, characterized in that: In S3, the positive electrode material is one of lithium metal, lithium cobalt oxide, and lithium nickel manganese cobalt oxide, and the solid electrolyte is one of a sulfide solid electrolyte and an oxide solid electrolyte.

8. The method for preparing a polymer solid electrolyte coated modified silicon-based negative electrode material according to claim 4, characterized in that: The solid electrolyte can be prepared into an electrolyte membrane or electrolyte layer by hot pressing, cold pressing or solvent volatilization. During the preparation of the positive electrode material, a conductive agent and a binder can be added as needed to improve the conductivity and mechanical strength of the positive electrode sheet. During the preparation of the solid electrolyte, the ion conductivity and mechanical properties of the solid electrolyte can be optimized by adjusting parameters such as the raw material ratio, the preparation process and the heat treatment conditions.

Citation Information

Cited By

  • Preparation method of solid-state battery silicon-based composite negative electrode material

    CN121709569A

  • High-rate silicon-based negative electrode solid-state battery and preparation method thereof

    CN122118102A